The Effect Of Sustainability, Liquidity, Leverage, And Firm Size On Firm Value With Profitability As A Moderating Variable (A Study Of Non-Bank Financial Sector Companies Listed On The Bursa Efek Indonesia During 2020–2024) - I Gede Komang Sunseno Indra Mukti; Andam Dewi Syarif (International Journal Labs, 2026)
This research aims to analyze the effect of sustainability, proxied by the Sustainability Report Disclosure Index (SRDI), liquidity, proxied by the Current Ratio (CR), leverage, proxied by the Debt to Equity Ratio (DER), and company size, proxied by Log Total Assets (SIZE), on company value, which is proxied by the Price to Book Value (PBV), with profitability, proxied by the Return on Equity (ROE), as a moderating variable. The research samples were selected using a purposive sampling method, with the population consisting of 58 non-bank financial sector companies listed on the Indonesia Stock Exchange for the period 2020–2024. The research sample comprised 17 listed companies that met the established criteria. The research method is quantitative, employing the regression method in the form of panel data regression analysis, as the data used is a combination of time series and cross-sectional data. The results of the study indicate that SRDI, CR, DER, SIZE, and the interaction of independent variables with the moderating variable jointly affect company value. Partially, CR, DER, and SIZE influence firm value, while SRDI and ROE have no effect. Meanwhile, ROE moderates the effect of CR and SIZE on firm value but does not moderate the effect of SRDI and DER.